Combined application of nano-DAP and conventional fertilizers improved agronomic and economic performance of rainfed maize, nutrient and energy use efficiency - Gopinath, K.A.; Visha Kumari, V.; Singh, V.K.; Shanker, A.K.; Reddy, K. Sammi; Kundu, S.; Chary, G. Ravindra; Bhargavi, B.; Rajkumar, B.; Lavanya, N.; Chandana, P.; Krupashankar, M.R.; et al. (Frontiers in Agronomy, 2025)
Efficient nitrogen (N) and phosphorus (P) management enhances crop yield while minimizing environmental impact. Nano-fertilizers are reported to ensure sustained nutrient release, optimize nutrient absorption and improve nutrient use efficiency, leading to higher crop productivity and profitability. A two year field trial was conducted under semi-arid conditions in India to evaluate the effect of foliar-applied nano-DAP on the growth, productivity, profitability and nutrient use efficiency of rainfed maize. The treatments comprised conventional fertilizers at varying N and P levels [0, 50, 75, and 100% recommended dose of N and P] with and without foliar application of nano-DAP. Application of 100% recommended NPK (90-45–45 N-P-K kg ha-1) through conventional fertilizers along with foliar sprays of nano-DAP (N100P100K+ nano-DAP) resulted in higher grain yield (3058 kg ha-1) and economic returns (US $ 473 ha-1). Notably, the N75P75K + nano-DAP treatment produced yield and economic returns comparable to those obtained with 100% recommended NPK, either alone or in combination with nano-DAP. This demonstrates that two foliar sprays of nano-DAP can reduce N and P inputs by 25% without compromising on yield or profitability. Higher agronomic use efficiency of N (26.9%) and P (48.4%), apparent recovery efficiency of N (42.6%) and P (11.3%) were also observed under N75P75K + nano-DAP. Furthermore, N75P75K + nano-DAP treatment reduced greenhouse gas (GHG) emissions by 24.5% and energy consumption by 15.4%, highlighting its potential for sustainable maize production with reduced environmental impact compared to N100P100K treatments.